Pengembangan Media Pembelajaran Digital Menggunakan Aplikasi Canva pada Mata Pelajaran IPAS di Kelas IV Sekolah Dasar - Siregar, Safwina Rizayani; Iraqi, Hana Shilfia; Zuardi, Zuardi; Syafitri, Serly (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to develop a valid, practical, and effective digital learning media based on Canva for teaching IPAS in fourth grade elementary school that can be used in the learning process. This type of research is development research (Research and Development) with the ADDIE development model. The trial subjects were conducted at UPTD SDN 35 Hutagodang, followed by research at UPTD SDN 02 Hutagodang, and then implemented at UPTD SDN 16 Hutagodang. The results of the development research of digital learning media based on Canva in IPAS learning for grade IV elementary school are valid with an average of 86.33% in the